The Analysis of Verbal Abuse within Socialization Ability of Preschoolers in Playproup Al Fattah Malang - Prima Dewi Kusumawati; Nadya Risky Aini Nasution (Journal Of Nursing Practice, 2022)
Background: Preschoolers are children with a phase of developing and learning new things quickly. The development phase begins with interacting with family and socializing with playmates in the social environment. The social environment can affect the development process of pre-school age children, for example the occurrence of verbal abuse in the social environment that has an impact on children's social development. Purpose: The purpose of this study was to determine the relationship between verbal abuse and the socialization ability of preschool children. Methods: The research design was cross sectional study and the sampling method was carried out by the total sampling method. The sample in this study was all 50 students of Playgroup Al Fattah Malang. Data analysis used SPSS program with Chi Square test. Results: It was found that 46% of children received verbal abuse in the low category, 38% in the medium category and 16% received verbal abuse in the high category and 76% of children had good socialization skills and 24% of children had poor socialization skills and through Chi Square test analysis with In the SPSS program, the value of Asymptotic Significance (2-sided) = 0.001 < 0.05, it means that H1 is accepted, or it is clear that there is a relationship between verbal abuse and the socialization skills of preschoolers in Playgroup Al Fattah Malang. Conclusion: It can be concluded that verbal abuse can result in barriers and disruptions to the socialization development of preschool children. Parents and teachers are expected to provide the right parenting to improve socialization skills in preschool age children.